Translation of nurse-initiated protocols to manage fever, hyperglycaemia and swallowing following stroke across Europe (QASC Europe): A pre-test/post-test implementation study. (March 2023) - Middleton, Sandy; Dale, Simeon; McElduff, Benjamin; Coughlan, Kelly; McInnes, Elizabeth; Mikulik, Robert; Fischer, Thomas; Van der Merwe, Jan; Cadilhac, Dominique; D'Este, Catherine; Levi, Christopher; Grimshaw, Jeremy M; et al.
Introduction: Poor adoption of stroke guidelines is a problem internationally. The Quality in Acute Stroke Care (QASC) trial demonstrated significant reduction in death and disability with facilitated implementation of nurse-initiated Methods: This was a multi-country, multi-centre, pre-test/post-test study (2017–2021) comparing post implementation data with historically collected pre-implementation data. Hospital clinical champions, supported by the Angels Initiative conducted multidisciplinary workshops discussing pre-implementation medical record audit results, barriers and facilitators to FeSS Protocol implementation, developed action plans and provided education, with ongoing support co-ordinated remotely from Australia. Prospective audits were conducted 3-month after FeSS Protocol introduction. Pre-to-post analysis and country income classification comparisons were adjusted for clustering by hospital and country controlling for age/sex/stroke severity. Results: Data from 64 hospitals in 17 countries (3464 patients pre-implementation and 3257 patients post-implementation) showed improvement pre-to-post implementation in measurement recording of all three FeSS components, all p  < 0.0001: fever elements (pre: 17%, post: 51%; absolute difference 33%, 95% CI 30%, 37%); hyperglycaemia elements (pre: 18%, post: 52%; absolute difference 34%; 95% CI 31%, 36%); swallowing elements (pre: 39%, post: 67%; absolute difference 29%, 95% CI 26%, 31%) and thus in overall FeSS Protocol adherence (pre: 3.4%, post: 35%; absolute difference 33%, 95% CI 24%, 42%). In exploratory analysis of FeSS adherence by countries' economic status, high-income versus middle-income countries improved to a comparable extent. Discussion and conclusion: Our collaboration resulted in successful rapid implementation and scale-up of FeSS Protocols into countries with vastly different healthcare systems. Graphical abstract